Lifting the Oil Curse : Improving Petroleum Revenue Management in Sub-Saharan Africa - Malothra, Harinder (International Monetary Fund, 2004)
How can a country turn oil revenues into a blessing rather than a curse? With growing international interest in new offshore oil deposits in sub-Saharan Africa, there is also greater scrutiny of the reasons why many oil-producing countries in the region have experienced disappointing economic performance over the past 20 to 30 years. This paper discusses the latest thinking on best-practice institutions and policies, compares this thinking with current practice in African oil-exporting countries, and presents a plan for the future, taking into account African policymakers'concerns.